A long-lived charge-separated state of spiro compact electron donor-acceptor dyads based on rhodamine and naphthalenediimide chromophores - Xiao, Xiao; Kurganskii, Ivan; Maity, Partha; Zhao, Jianzhang; Jiang, Xiao; Mohammed, Omar F; Fedin, Matvey (Chemical science (Cambridge), 2022)
Spiro rhodamine (Rho)-naphthalenediimide ( NDI ) electron donor-acceptor orthogonal dyads were prepared to generate a long-lived charge separation (CS) state based on the electron spin control approach, i.e. to form the 3 CS state, not the 1 CS state, to prolong the CS state lifetime by the electron spin forbidden feature of the charge recombination process of 3 CS → S 0 . The electron donor Rho (lactam form) is attached via three σ bonds, including two C-C and one N-N bonds ( Rho-NDI ), or an intervening phenylene, to the electron acceptor NDI ( Rho-Ph-NDI and Rho-PhMe-NDI ). Transient absorption (TA) spectra show that fast intersystem crossing (ISC) (<120 fs) occurred to generate an upper triplet state localized on the NDI moiety ( 3 NDI*), and then to form the CS state. For Rho-NDI in both non-polar and polar solvents, a long-lived 3 CS state (lifetime τ = 0.13 μs) and charge separation quantum yield ( Φ CS ) up to 25% were observed, whereas for Rho-Ph-NDI ( τ T = 1.1 μs) and Rho-PhMe-NDI ( τ T = 2.0 μs), a low-lying 3 NDI* state was formed by charge recombination (CR) in n -hexane (HEX). In toluene (TOL), however, CS states were observed for Rho-Ph-NDI (0.37 μs) and Rho-PhMe-NDI (0.63 μs). With electron paramagnetic resonance (EPR) spectra, weak electronic coupling between the Rho and NDI moieties for Rho-NDI was proved. Time-resolved EPR (TREPR) spectra detected two transient species including NDI -localized triplets (formed via SOC-ISC) and a 3 CS state. The CS state of Rho-NDI features the largest dipolar interaction (| D | = 184 MHz) compared to Rho-Ph-NDI (| D | = 39 MHz) and Rho-PhMe-NDI (| D | = 41 MHz) due to the smallest distance between Rho and NDI moieties. For Rho-NDI , the time-dependent e , a → a , e phase change of the CS state TREPR spectrum indicates that the long-lived CS state is based on the electron spin control effect. Spiro compact rhodamine-naphthalenediimide electron donor-acceptor dyads show a long-lived charge separated state (lifetime: 0.72 μs) based on the electron spin control effect were reported.